Toward an integrative model of moral‐value perception. (17th March 2021) - Young, Robert L.
Abstract: Moral‐value perception occurs when sensory perception is directed by cognitive schemas, which selectively sample information in objects and events that represent personally valued means or ends. As a result of the perception of such value representations people experience affect ranging from strongly negative to strongly positive. If one's schemas direct attention to elements of objects or actions that verify schematic expectations, and spark little of no noticeable affect, the new information automatically produces minor alterations of the schema. However, if attention is directed or drawn to information that produces strong affect, and is contradictory of activated schemas, one is likely to engage in conscious assessment, through which the information is re‐conceptualized in a way that preserves schematic integrity. Based on multidisciplinary analysis, this paper (1) addresses the ways in which the perception of things within the natural world are represented in moral‐value perceptions, (2) identifies important cognitive, affective and emotional processes involved in the ongoing experience of such perception, and (3) illustrates some of the ways in which moral‐value perceptions influence moral assessments and judgements.